Genetic Relatedness Analysis Of Little Millet (Panicum Sumatrense Roth. Ex Roem & Schult.) Using Rapd Markers (Applied Biological Research, 2023)
Little millet, having a significant nutritional value, has not been exploited to its true potential so remains underutilized. The molecular relatedness analysis of  available genotypes is a crucial step in crop improvement and germplasm  conservation of millets. The present study evaluated genetic relatedness among  16 little millet genotypes, collected from Dang region of Gujarat (India), using random amplified polymorphic DNA (RAPD) markers. Initially, a total of 120  RAPD primers were screened, of which only 25 RAPD primers produced  distinct bands so were used for further analysis. RAPD analysis with selected 25 decamer primers amplified a total of 193 bands with amplicon sizes in between  50-2392 bp. There were 126 polymorphic bands (64.25%) with mean  polymorphic bands of 5.04 per primer. The maximum marker index of 41.25,maximum polymorphic information content of 0.59 and maximum RAPD  primer index of 5.69 were recorded in primers OPC-13, OPC-17, and OPA-12,  respectively. The RAPD primers OPA-12, OPC-13, and OPC-17 proved most efficient for genetic relatedness analysis in little millet. The Jaccard's similarity  coefficient among the genotypes was in the range of 0.53 to 0.98 revealia  moderate genetic diversity among the available genotypes. The dendrogramdivided 16 genotypes of little millet into two major clusters and further sub clusters, demonstrating that RAPD technique was effective to distinguish the  studied genotypes. The dendrogram and PCoA analysis revealed that genotypes  WV-151 and WV-161 were highly diverse. These genotypes along with genetic  relatedness established in this study can be exploited in future little millet  improvement programs with conventional and molecular breeding methods.
Keywords: Genetic relatedness; little millet; molecular marker; RAPD